Pengembangan Media Pembelajaran Geografi Berbentuk Majalah Digital Dengan Materi Dinamika Litosfer Untuk Siswa Kelas X SMA Negeri 2 Limboto - Samaili, Suardi K; Lihawa, Fitryane; Mohamad, Nurdin (Universitas Negeri Gorontalo, 2025)
This research is a study on the development of learning media. The purpose of this research is to develop a digital magazine learning medium for lithosphere dynamics material. This research uses the ADDIE model development research method as an approach in compiling the learning media. Media validation was carried out by material experts, media experts, and learning experts. This learning media was tested on a limited scale with a total of 31 students taken from schools, namely SMA Negeri 2 Limboto, using an instrument in the form of a questionnaire. Research data was obtained from the results of validators which indicated that this learning media was declared suitable for use and included in the very valid category. Validation by material experts obtained a percentage value of 87.27%, which is included in the very valid category, from media experts obtained a percentage value of 80%, which is in the valid category, and learning experts gave a very valid value with a percentage of 91.11%. Meanwhile, the average student response to the learning media was 82.18%, which is included in the valid category. Based on these results, digital magazine-based learning media is declared feasible and effective for use as an alternative learning medium in supporting the geography learning process because it received a good response from students, especially in the Lithosphere Dynamics material